2011
DOI: 10.3348/kjr.2011.12.5.602
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antiangiogenic Effects of a New Synthetic Candidate Drug KR-31831 on Xenografted Ovarian Carcinoma Using Dynamic Contrast Enhanced MRI

Abstract: ObjectiveThe purpose of this research was to investigate the anti-angiogenic inhibitory effect of KR-31831, a newly developed anti-angiogenic agent, on an in vivo human ovarian carcinoma model using dynamic contrast-enhanced (DCE) MRI.Materials and MethodsXenografted ovarian tumors were established by subcutaneous injection of SKOV3 cells into mice. The mice were treated daily with KR-31831 at 50 mg/kg for 21 days. Tumor tissues were excised corresponding to the DCE-MRI sections for evaluation of MVD with CD31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The relationships of these two parameters with physiological biomarkers of ovarian tumor malignancy have been confirmed previously . The relevance of these two parameters to the pathophysiological properties of tumors can be explained by the highly permeable tumor neovasculature that is aggravated when the tumor advances into a malignant form . Therefore, by inspecting DCE‐MRI curves in malignant lesions, a steep slope of enhancement, ie, higher wash‐in‐rate and smaller initial time to enhancement peak, denoting the time by which the contrast agent has permeated into the microvasculature, can be observed.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The relationships of these two parameters with physiological biomarkers of ovarian tumor malignancy have been confirmed previously . The relevance of these two parameters to the pathophysiological properties of tumors can be explained by the highly permeable tumor neovasculature that is aggravated when the tumor advances into a malignant form . Therefore, by inspecting DCE‐MRI curves in malignant lesions, a steep slope of enhancement, ie, higher wash‐in‐rate and smaller initial time to enhancement peak, denoting the time by which the contrast agent has permeated into the microvasculature, can be observed.…”
Section: Discussionmentioning
confidence: 56%
“…5,7,21 The relevance of these two parameters to the pathophysiological properties of tumors can be explained by the highly permeable tumor neovasculature that is aggravated when the tumor advances into a malignant form. 22 Therefore, by inspecting DCE-MRI curves in malignant lesions, a steep slope of enhancement, ie, higher wash-in-rate and smaller initial time to enhancement peak, denoting the time by which the contrast agent has permeated into the microvasculature, can be observed. This finding is consistent with several related studies where WIR and/or TTP (with other equivalent terminologies) have been reported as helpful indicators for discriminating benign and malignant ovarian masses.…”
Section: Discussionmentioning
confidence: 99%
“…DCE‐MRI has recently been used to monitor therapeutic responses to new treatment methods and to evaluate the effects of new antiangiogenic drugs in preclinical and clinical studies 3 , 4 , 5 , 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…Also, it is not clear whether it is appropriate to include vascular tumors, such as hemangiomas in the benign tumor group. Further research using various parametric imaging techniques that are less reliant on ROI areas and 3D sequences covering the whole tumor may overcome these deficiencies, while further correlation with quantitative pharmacokinetic DCE-MRI parameters is also warranted (15-18). Lastly, one must be careful when comparing DCE-MRI study results as dynamic MRI examinations from different measurement conditions or scanners are difficult to compare with each other (19).…”
Section: Discussionmentioning
confidence: 99%